Direct Imaging of High‐Frequency Multimode Spin Wave Propagation in Cobalt‐Iron Waveguides Using X‐Ray Microscopy beyond 10 GHz. Issue 12 (5th October 2020) - Träger, Nick; Gruszecki, Paweł; Lisiecki, Filip; Förster, Johannes; Weigand, Markus; Wintz, Sebastian; Stoll, Hermann; Głowiński, Hubert; Kuświk, Piotr; Krawczyk, Maciej; Gräfe, Joachim
Abstract : Not only in fundamental wave physics but also in technical areas such as radar and communication systems, high‐frequency magnonics is increasingly attracting attention. Here, time‐resolved scanning transmission X‐ray microscopy is used to directly image high‐frequency spin wave propagation in cobalt‐iron waveguides at excitation frequencies above 10 GHz. In addition, an excitation technique is presented, which allows for versatile pump–probe experiments with radio frequency currents up to 30 GHz. With this approach, a global sinusoidal magnetic field excitation is applied to induce spin waves from the waveguide edges. Amplitude, relative phase, and k ‐space information as a function of excitation frequencies and static external fields are observed, matching the theoretical predictions for confined waveguide structures. In doing so, the foundation for high‐frequency multimode spin wave excitation and propagation at the nanoscale is laid, which can be a prospective path in radar and communication systems. Abstract : Time‐resolved X‐ray microscopy is used to image spin waves in magnonic waveguides at the excitation frequencies above 10 GHz. An oscillating global magnetic field induces magnons within the waveguide where both symmetric and antisymmetric spin wave modes are detectable. In addition, a unique excitation setup is introduced, which is capable of generating arbitrary radio frequency currents up to 30 GHz.